What patient assessment skills are required by pharmacists prescribing systemic anti-cancer therapy? A consensus study. (December 2019) - Allison, Jennifer; Fisher, Julie; Souter, Caroline; Bennie, Marion
Background: In the UK, pharmacist independent prescribers can prescribe for any condition within their clinical competence including systemic anti-cancer therapy. Competency frameworks have been developed but contain little detail on the patient assessment skills pharmacist independent prescribers require to prescribe systemic anti-cancer therapy with concern in the literature over current training on these skills. Aim: To gain consensus on the patient assessment skills required by pharmacist independent prescribers prescribing systemic anti-cancer therapy for genitourinary cancer (prostate and renal) and lung cancer across National Health Service Scotland. Method: Two phases were performed to generate patient assessment skill consensus. Initially, the Nominal Group Technique was performed within a local cancer network by discussion and participant ranking within genitourinary and lung cancer multi-disciplinary teams. Where consensus was achieved, patient assessment skills were carried forward to try to achieve national (National Health Service Scotland) consensus using a two-round Delphi questionnaire. Results: Of the 27 patient assessment skills, consensus was gained for 21 and 23 patient assessment skills in the genitourinary and lung Nominal Group Technique groups, respectively. Within the genitourinary and lung national groups, 13/21 and 18/23 patient assessment skills were agreed as required for a pharmacist independent prescriber to prescribe systemic anti-cancer therapy in genitourinary and lung cancer, respectively. Eight common patient assessment skills were identified as core skills. Reasons for not reaching consensus included pharmacist independent prescriber competence, knowledge, skills and the roles and responsibilities of pharmacist independent prescribers within the multi-disciplinary team. Conclusion: We identified the core and specific patient assessment skills required to prescribe systemic anti-cancer therapy within two tumour groups. Further work is necessary to develop patient assessment skill competency frameworks, training and assessment methods and to redefine the roles of pharmacist independent prescribers within the multi-disciplinary team.